Effect of early weaning on the growth of Libyan Barbary sheep - Zayid, Aabdallah Aabdalrahman; Majid, Eiad (Al-Mukhtar Journal of Sciences, 1992)
The experimental work was carried out in the sheep experimental station at al-fateh university, tripoli. Lambs born during noember. December were assigned into three groups according to their weaning age. Groups i, ii and iii were weaned at 60,90 and 120 days of age, respectively. All lambs were identified, eartagged and weighted within 12 hours after birth. Live weights were recorded on all Lambs at 60,90 and 120 days and each two weeks then after till the lambs reached 7 months of age. At weaning of each group the lambs were separated from their dams and started on daily al. lowance of 200g oncentrate mixture Containing 14% C.P. that increased gradually to reach 600 g / head / day. The least squares procedure for data with unequal Subclass numbers was used in the analysis of all weights recorded on lambs. Two statistical models were adopted. Results indicated that weaning at 60 days of age could be prac. ticed in this breed without affecting adversely the performance of lambs at marketing age (7 months). Further investigations are recommended as far as the effect of early weaning on the performance of lambs at breeding age and its effect on ewe performance.